Pacific Islands Coconut Oil Power Generation : A How-To Guide for Small Stationary Engines - World Bank (Washington, DC, 2017)
This guide has been written to assist anyone interested in running small stationary diesel powered engines on coconut oil. It is intended to be a 'how-to' guide to provide with relevant information of every aspect of fuelling an engine with coconut oil. The guide is specifically written with small (less than about 50 kVA) diesel generators in mind. While the information and principles can be applied to all diesel engines, there are additional complicating factors to consider when applying to a vehicle, for example. It must be noted also, that this manual is intended for stationary applications that typically involve few stop-starts, longer running times and consistent loads. Diesel engines that stop-start regularly and unpredictably (eg. car engine or back up generator) are outside the scope of this guide. The technical considerations for running a diesel engine on coconut oil, or any vegetable oil for that matter, are not particularly complex. The concept of powering a diesel engine with vegetable oil is, after all, as old as the diesel engine itself. To do it successfully, however, and particularly with today's modern diesel engines, several key elements of the fuel delivery and combustion system must be suitable or made suitable. If these elements are not the engine will be damaged and it will ultimately lead to premature engine failure.